CPWF Annual Report 2007 - CGIAR Challenge Program on Water and Food (CGIAR Challenge Program on Water and Food, 2008)
The CGIAR Challenge Program on Water and Food (CPWF) brings together scientists, development specialists, and communities, in nine river basins across Africa, Asia and Latin America, to address challenges of water scarcity, food security and poverty. Some CPWF projects seek to develop innovative technologies, new institutional arrangements, or improved policies. Other projects strategically aim to better define issues and challenges, understand processes and principles, and develop more appropriate research tools and methods. All of them are conducted by teams formed from partnerships of notable scope, breadth and diversity. In 2007, the CPWF successfully concluded the selection of eight gap‐filling projects in a second competitive call and a second set of six Basin Focal Projects. Consequently the CPWF research portfolio expanded to encompass 67 funded projects, including 11 Basin Focal Projects in total, and 14 Small Grants Projects. Naturally the Challenge Program’s diverse partnerships continue as an integral feature of its work. Due to interactions between partners of different backgrounds and approaches, CPWF relationships sometimes produce surprising results in both the conduct and interpretation of the scientific research. With the addition of the new 2007 projects, a total of 213 institutions now share their expertise within Program projects and an even larger group sharing within the CPWF community. The Program had a very full year undergoing a vigorous External Review as well as placing focus on moving CPWF research towards reported results. The program is now producing good quality science, both by “conventional” publication measures and in its progress towards impact. Based on CPWF work to date, approximately 180 peer‐reviewed papers have been received in journals, books and research reports, including CPWF contributions to publications of the Comprehensive Assessment on Water Management in Agriculture. For the 2007 CPWF Annual Report, the five Themes, which work across the nine basins, integrated their findings under four topics of international public value: 1. Water productivity, multiple uses and technical innovation 2. Benefit sharing and institutional innovation 3. Global change and policy 4. Unique contribution of the CPWF Impact and progress can also be illustrated through the inspiring results of various individual projects. For example: • CPWF Project 10 on Coastal Resources Management is achieving impact at provincial level in Vietnam. Successful lessons from the project have been picked up in the Ganges Basin, as well as other locations as a result of two delta scientific conferences, organized and hosted by the project. • The External Review had very positive comments about the potential of the CPWF on the basis of two projects the review chair visited in India. For Project 34 on Fish Production in Tropical Reservoirs, the comment was: “An intensive interaction with the local fishers indicated that even though the project is comparatively new, their lives have already been 2 | P a g e 3 | P a g e positively impacted upon, and they are excited by the results of the project, which may improve their living standards dramatically.” • The concept of Multiple‐Use Systems of Project 28 has proved important to the CPWF. Initial successes have influenced the development of new water policies in South Africa as well as provided viable new production and water‐use alternatives for farmers in parts of Nepal, Thailand, Bolivia and South Africa. • CPWF’s Multiple Agent Modelling Project 25 has made considerable progress to developing new ways of facilitating and implementing negotiation between small‐scale resource users. Early methodological results from the project received an award from the journal Ecology and Society as “the most novel paper that integrates different streams of science to assess fundamental questions in the ecological, political, and social foundations for sustainable social‐ecological systems.” • CPWF Project 50 on Water Governance in the Mekong, has employed an innovative system that combines low‐cost, targeted research, with an elaborate advocacy system employing the mass media, directly designed to achieve impact and influence policy. The portfolio includes research streams which have also borne robust insights and impacts this year: the Basin Focal Projects report that some of the most exciting results have come from their comparative work on water use and poverty across basins, and the Program’s Participatory Impact Pathways Analysis initiative has considerably strengthened project outputs and outcomes. In 2007 thirteen of the CPWF’s 14 Small Grants for Impact Projects concluded, many with very encouraging results for small producers that illustrate the impact opportunities of water‐for‐food technologies, including the system of rice intensification (SRI) in eastern Thailand and small‐scale vegetable production in Cambodia. Additionally important efforts in CPWF Capacity Building were funded and implemented, principally in West Africa in partnership with IFS and French‐supported CPWF projects in Mekong, Limpopo and Niger.